2022
DOI: 10.1093/cvr/cvac060
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils protect pressure overload- and β-adrenoreceptor agonist-induced cardiac hypertrophy

Abstract: Aims Blood eosinophil (EOS) counts and EOS cationic protein (ECP) levels associate positively with major cardiovascular disease (CVD) risk factors and prevalence. This study investigates the role of EOS in cardiac hypertrophy. Methods and results A retrospective cross-section study of 644 consecutive inpatients with hypertension examined the association between blood EOS counts and cardiac hypertrophy. Pressure overload- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…We have recently reported a role of EOS in AAA and cardiac repair during myocardial infarction and cardiac hypertrophy. [ 11,44,60 ] ILC2 may use the same mechanisms demonstrated in this study to produce IL5 to control EOS development as an indirect mechanism that protects hearts from infarct injury‐associated cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 86%
“…We have recently reported a role of EOS in AAA and cardiac repair during myocardial infarction and cardiac hypertrophy. [ 11,44,60 ] ILC2 may use the same mechanisms demonstrated in this study to produce IL5 to control EOS development as an indirect mechanism that protects hearts from infarct injury‐associated cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 86%
“… 41 Human ECP and EDN share similar tertiary sequence structure and surface charges with mEar1. 17 mEar1 binding on BMPR-1A/1B and less efficiently on BMPR-2 suggests that human ECP and EDN also use BMPR-1A, BMPR-1B, and possibly BMPR-2 as their receptors on vascular SMC. After human vascular SMCs were treated with ECP followed by immunoprecipitation with ECP antibody, we performed immunoblot analyses with various antibodies and found that human ECP formed complexes with BMPR-1A and BMPR-1B, but not BMPR-2 or TGFBR1/2 ( Figure 7A ).…”
Section: Resultsmentioning
confidence: 99%
“…Our recent study showed that donor eosinophils remained high for 7 days after adoptive transfer in recipient mouse hearts but lowered after 14 days. 17 Therefore, each recipient mouse received six doses of 1 × 10 7 donor eosinophils by intravenous (i.v.) injection starting at day 0 before being fed an atherogenic diet and two weeks thereafter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, animal studies have suggested that increased eosinophils play a role in tissue protection against heart and liver injury. [33][34][35] Thus, it is also possible that interstitial eosinophilic aggregates in the kidney represent a protective response to an active disease status. Whether eosinophils play a protective or harmful role may depend on the target organs and the specific pathological context.…”
Section: Discussionmentioning
confidence: 99%